The Insanity of Kenya’s ‘Guilty but Insane’ Verdict - Kang'Ethe, Mitchelle (Strathmore Law Review, 2021)
A person may be insane while committing an unlawful act, leading them to raise the defence of insanity in court. This defence argues that the person’s illness prevented them from having the criminal intent needed to satisfy the mens rea requirement for criminal responsibility. The successful establishment of this defence in Kenya leads to the court issuing a special verdict of ‘guilty but insane’ (GBI). This verdict sees that the defendant is incarcerated in a place of safe custody where they can be treated for the illness that contributed to their commission of the offence. While isolation and treatment of the defendant form the primary aims of the verdict, this paper demonstrates that they are barely achieved in Kenya. This is because the conditions crucial to the verdict’s implementation–medication and therapy, a place of custody and the presence of psychiatrists–are wanting in the country. After examining the institutional barriers to the realisation of the verdict’s objectives, the paper studies various responses to these challenges by Kenya and Ghana. It finds solutions that promote the realisation of the verdict’s aims such as the provision of educational opportunities in forensic psychiatry.